Extracted c-Al2O3 from aluminum dross as a catalyst support for glycerol dry reforming reaction - Nurul Asmawati, Roslan; Sumaiya, Zainal Abidin; Nur Shafiqah, Nasir; Chin, Sim Yee; Y.H., Taufiq-Yap (Elsevier, 2021)
The utilization of extracted c-Al2O3 (EGA) from aluminum dross as catalyst support in glycerol dry reforming reaction (GDR) has been investigated in this current study. In this study, three main stages were evaluated which are; (i) extraction of c-Al2O3; (ii) preparation and characterizations of Ni-based catalyst supported on EGA and (iii) utilization of EGA as catalyst support in the GDR reaction. In the first stage, c-Al2O3 with the specific surface area of 156.5 m2 g1 was successfully extracted before used as catalyst support. Then, 10%Ni/EGA catalyst with 108.3 m2 g1 surface area was prepared by wet impregnation method. The glycerol conversion and hydrogen yield achieved in the third stage were 22% and 15% respectively. The results can be attributed to the high specific surface area of EGA, which enhanced the dispersion of Ni particles on the catalyst matrix.